The Funeral of Mr. Wang : Life, Death, and Ghosts in Urbanizing China. - Kipnis, Andrew B. (University of California Press, 2021)
A free open access ebook is available upon publication. Learn more atwww.luminosoa.org. In rural China funerals are conducted locally, on village land by village elders. But in urban areas, people have neither land for burials nor elder relatives to conduct funerals. Chinese urbanization, which has increased drastically in recent decades, involves the creation of cemeteries, state-run funeral homes, and small private funerary businesses. The Funeral of Mr. Wang examines social change in urbanizing China through the lens of funerals, the funerary industry, and practices of memorialization. It analyzes changes in family life, patterns of urban sociality, transformations in economic relations, the politics of memorialization, and the echoes of these changes in beliefs about the dead and ghosts.